2018
DOI: 10.1038/s41375-018-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

The AP-1-BATF and -BATF3 module is essential for growth, survival and TH17/ILC3 skewing of anaplastic large cell lymphoma

Abstract: Transcription factor AP-1 is constitutively activated and IRF4 drives growth and survival in ALK+ and ALK– anaplastic large cell lymphoma (ALCL). Here we demonstrate high-level BATF and BATF3 expression in ALCL. Both BATFs bind classical AP-1 motifs and interact with in ALCL deregulated AP-1 factors. Together with IRF4, they co-occupy AP-1-IRF composite elements, differentiating ALCL from non-ALCL. Gene-specific inactivation of BATFs, or global AP-1 inhibition results in ALCL growth retardation and/or cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 64 publications
7
89
0
Order By: Relevance
“…ALCL showed high expression of IL17A, IL17F and RORct transcripts, which are associated with normal Th17 cells (Iqbal et al, 2010). This has been substantiated in other work: analysis of ALCL cell lines showed that basic leucine zipper ATF-like transcription factor (BATF) and BATF3 established a Th17 gene expression pattern in ALCL cell lines (Schleussner et al, 2018). One effect of the t(2;5)(p23;q35) chromosomal translocation, which is found in ALK + ALCL, is to suppress GATA3 and Th2 gene expression while promoting Th17 genes (Matsuyama et al, 2011).…”
Section: Are Non-tfh Ptcl-nos Derived From Other Normal Tcell Subsets?supporting
confidence: 60%
“…ALCL showed high expression of IL17A, IL17F and RORct transcripts, which are associated with normal Th17 cells (Iqbal et al, 2010). This has been substantiated in other work: analysis of ALCL cell lines showed that basic leucine zipper ATF-like transcription factor (BATF) and BATF3 established a Th17 gene expression pattern in ALCL cell lines (Schleussner et al, 2018). One effect of the t(2;5)(p23;q35) chromosomal translocation, which is found in ALK + ALCL, is to suppress GATA3 and Th2 gene expression while promoting Th17 genes (Matsuyama et al, 2011).…”
Section: Are Non-tfh Ptcl-nos Derived From Other Normal Tcell Subsets?supporting
confidence: 60%
“…These results suggested that BATF may regulate NSCLC cell proliferation and apoptosis in vitro. A number of studies provide support that BATF may play an important role in the development of different types of cancer, including colon cancer, lymphoma and multiple myeloma (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the AP-1 gene effects cell survival, differentiation and proliferation (14,15). An increasing number of studies suggest that BATF may affect cancer development (16)(17)(18). However, the functional mechanisms of BATF in NSCLC are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…BATF-3 is highly expressed in CD30 + CHL, although it relies on additional AP-1 cofactors to dimerize, as BATF family members lack a transcriptional activation domain [ 89 , 90 , 91 ]. Indeed, co-immunoprecipitation and mass spectrometry revealed that BATF-3 directly interacts with JUN and JUNB in HRS cells, which in turn activates MYC transcription by directly binding to its promoter [ 88 , 92 ]. This novel oncogenic STAT–BATF-3/JUN–MYC signalling axis seems to be essential for HRS cell survival ( Figure 2 ) [ 88 ].…”
Section: Ap-1 Tfs In Classical Hodgkin Lymphoma (Chl)mentioning
confidence: 99%
“…In particular, JUNB or c-JUN expression protects cells from apoptosis, thereby enhancing cellular proliferation and colony formation [ 23 , 71 , 121 , 123 , 125 ]. Given the activity of c-JUN, JUNB, FRA-2, and ATF-3 in ALCL, it is likely that other AP-1 activating factors play a role in lymphomagenesis [ 92 , 118 ].…”
Section: Involvement Of Ap-1 Tfs In the Pathogenesis Of Cd30 mentioning
confidence: 99%